A timely update of global COVID-19 vaccine development - Linda S. Klavinskis; Margaret A. Liu; Shan Lu (Emerging Microbes and Infections, 2020)
ABSTRACTThis commentary provides an overview and links to presentations of a recent virtual congress series organized by the International Society for Vaccines (ISV) focused on COVID-19 vaccines. The series provided the academic community and vaccine developers as well as the wider general public with balanced information of the global response and resources for COVID-19 vaccines under development featuring: 1) NGOs and the regulatory perspective, 2) the status of vaccine development efforts, and 3) panel discussions to present and discuss challenges. ISV is a non-profit scientific organization whose members work on all areas relevant to vaccines. ISV plans to host additional virtual symposia including regional meetings and incorporating other topics along with COVID-19 vaccines.